2015
DOI: 10.1159/000370121
|View full text |Cite
|
Sign up to set email alerts
|

Allergogenic Profile in Patients with Different Subtypes of Chronic Rhinosinusitis with Nasal Polyps

Abstract: Aims: The aim of this study was to analyze the relationship between allergy and different subtypes of chronic rhinosinusitis with nasal polyps (CRSwNP). Methods: A total of 83 patients with CRSwNP and 20 patients with nasal septum deviation (NSD) as controls were enrolled in our study. Nasal tissue was obtained from all subjects during surgery. Hematoxylin and eosin staining was performed and the CRSwNP cases were classified into eosinophilic nasal polyps (ENP) and noneosinophilic nasal polyps (nENP) cases acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Complicating this picture, rates of systemic atopy vary between eosinophilic and non‐eosinophilic CRSwNP populations 1392 . Additionally, local production of specific IgE is seen in the absence of systemic atopy 1393 .…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…Complicating this picture, rates of systemic atopy vary between eosinophilic and non‐eosinophilic CRSwNP populations 1392 . Additionally, local production of specific IgE is seen in the absence of systemic atopy 1393 .…”
Section: Chronic Rhinosinusitis With Nasal Polyps (Crswnp)mentioning
confidence: 99%
“…Additionally, an allergen challenge could increase periostin expression in the airway epithelium, subepithelium, smooth muscle, and inflammatory cells 31 , and periostin has been shown to act on eosinophils and enhance their recruitment to lesions 32 . In our recent study, we found that ENPs were associated with Th2-mediated allergic disease and allergen sensitization 18 . The periostin-rich microenvironment develops in areas that are associated with insult, and exposure to allergens in atopic diseases can be considered an insult 33 .…”
Section: Discussionmentioning
confidence: 96%
“…Evidence suggests that periostin could promote angiogenesis by upregulating VEGF through the focal adhesion kinase (FAK) or the signal-regulated kinase 1/2 (ERK 1/2) mediated signaling pathways 14 , 15 . To date, some investigators have proposed that periostin is produced locally in the sinonasal tissues and might contribute to polyp formation 16 , 17 ; meanwhile, we had found that patients with ENP were more likely to be atopic 18 , so we speculate that periostin might play an important role in tissue remodeling in NP via inducing VEGF, RANTES and eotaxin-2 production. However, current evidence for the relationships among VEGF, RANTES, eotaxin-2 and periostin and various nasal disorder subtypes is scarce, and their importance in different subtypes of NP pathogenesis is not well understood.…”
Section: Introductionmentioning
confidence: 81%
“…Frequently tested aeroallergens ranging from molds, trees, weeds, grass, animal dander are usually secondary to the house dust mite (HDM) as the most frequent offender. 5 While some studies have purported direct associations between CRS volunteers and allergic sensitization, there is not a definitive correlation between the two. For instance, in a study by Gutman 2004 of 48 voluntary participants with CRS and recurrent acute rhinosinusitis, 57.4% had a positive allergy test with the majority being sensitive to more than one allergen (most commonly perennial allergens, mold and dust mites).…”
Section: Aeroallergensmentioning
confidence: 99%